2010
DOI: 10.1590/s0004-282x2010000300005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of antioxidants (ascorbic acid or α-tocopherol) on seizures and brain damage induced by pilocarpine in rats

Abstract: Temporal lobe epilepsy is the most common form of epilepsy in humans. Oxidative stress is a mechanism of cell death induced by seizures. Antioxidant compounds have neuroprotective effects due to their ability to inhibit free radical production. The objectives of this work were to comparatively study the inhibitory action of antioxidants (ascorbic acid or α-tocopherol) on behavioral changes and brain damage induced by high doses of pilocarpine, aiming to further clarify the mechanism of action of these antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 34 publications
(50 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, some of these amino acids have metabolic roles in brain, in addition to their as neurotransmitter functions 6 . The changes we have found do appear to be secondary to any general derangement produced by seizures in amino acid metabolism, for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some of these amino acids have metabolic roles in brain, in addition to their as neurotransmitter functions 6 . The changes we have found do appear to be secondary to any general derangement produced by seizures in amino acid metabolism, for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies on the health benefits of tocopherols have been reported (Ishihara et al 2008;Tomé et al 2010). Tocopherols can be biosynthesized by plants (DellaPenna and Pogson 2006) and accumulate in the edible plant oil because of their high lipophilicity (Sattler et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the deleterious effects of free radicals can be inhibited by the presence of antioxidant substances such as ascorbic acid (Tomé et al 2010b), alpha-tocopherol , lipoic acid (Freitas 2009) and ubiquinone (Santos et al 2010), which can inhibit the occurrence of lipid peroxidation and nitrite formation. However, the search for new antioxidant compounds with therapeutic potential for the treatment of neurodegenerative diseases is a complex and very challenging process.…”
Section: Introductionmentioning
confidence: 99%